2007
DOI: 10.3748/wjg.v13.i6.916
|View full text |Cite
|
Sign up to set email alerts
|

Self-expandable metallic stents for palliation of patients with malignant gastric outlet obstruction caused by stomach cancer

Abstract: AIM:To ascertain clinical outcome and complications o f s e l f-e x p a n d a b l e m e t a l s t e n t s fo r e n d o s c o p i c palliation of patients with malignant obstruction of the gastrointestinal (GI) tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 26 publications
(32 reference statements)
1
23
0
Order By: Relevance
“…Pancreatic cancer is usually the most common cause, and the duodenum is a common main site of an obstruction. A few reports on these stents dealt exclusively with gastric cancer [6,7,16]. Our study included only patients with a malignant gastric outlet obstruction caused by primary gastric cancer, and patients with other malignancies or recurrent cancer of the anastomosis site were excluded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatic cancer is usually the most common cause, and the duodenum is a common main site of an obstruction. A few reports on these stents dealt exclusively with gastric cancer [6,7,16]. Our study included only patients with a malignant gastric outlet obstruction caused by primary gastric cancer, and patients with other malignancies or recurrent cancer of the anastomosis site were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports on the use of a SEMS for a malignant gastroduodenal obstruction included heterogeneous patient groups with different cancers such as pancreaticobiliary cancer, duodenal cancer, and gastric cancer. Some studies have reported on the endoscopic use of a SEMS for malignant gastric outlet obstructions caused by primary gastric cancer [6,7]. The biological activity and response to chemotherapy or radiotherapy can differ according to the type of cancer, which might affect the stent patency and clinical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Kim et al [10] , restenosis occurring at less than 4 wk after stent placement was found in 5/43 patients (11.6%), which was successfully treated with placement of covered stents in the new stenotic area. Stentrelated problems requiring treatment occurred in 17 patients (32.1%) during the followup period (mean 145 d, range 4718 d).…”
Section: Complicationsmentioning
confidence: 95%
“…nausea, vomiting, abdominal distention, and reflux), which occurred in 29/32 patients (90.6%), with no symptomatic improvement in three patients. Kim et al [10] also used symptomatic improvement as the measure of clinical success in their assessment of outcomes after SEMS placement in 53 patients with gastric outlet obstruction due solely to gastric cancer, in which they reported a success rate of 81.8%.…”
Section: Efficacy and Outcomesmentioning
confidence: 99%
“…The median duration of stent patency in the upper GI tract are reported around 55 to 307 days in most studies and are not significantly different between covered and uncovered types or among products from various companies, except for the esophageal cancer. In pyloric obstruction, the reported patency rates were 71% at 4 weeks, 61% at 8 weeks, and 33% at 6 months, and in cardiac obstruction including esophageal cancer, the rates were 94% at 4 weeks, 78% at 3 months, and 67% at 6 months in previous studies 1,4,20,21. When comparing stents with surgical bypass in malignant upper GI obstruction, stent showed many advantages in terms of less invasiveness and complications, shorter hospital stay, and lower cost 22-25.…”
Section: Clinical Outcomes Of Stents In the Upper Gi Tractmentioning
confidence: 80%